Seizure threshold, hormones and anti epileptic drugs - Harsono, Harsono (Universa Medicina, 2008)
The concept of seizure threshold holds that everyone has a certain balance between excitatory and inhibitory forces in the brain. A low seizure threshold makes it easier for epilepsy to develop and easier for someone to elicit single seizure. The opposing effects of estrogen (proconvulsant) and progesterone (anticonvulsant) on seizure threshold have been noted in animal and human studies. Estrogen has been shown to lower the seizure threshold. In contrast to estrogen, several studies have confirmed the anticonvulsive effects of progesterone and its metabolite. Anti-epileptic drugs (AEDs) are used to prevent or interrupt seizures. Limitation of sustained repetitive neuronal firing via blockade of voltage-dependent sodium channels, enhancement of GABA-mediated inhibition, and blockade of glutamatergic excitatory neurotransmission are the mechanisms of anti-epileptic drugs in preventing seizures. AEDs that induce hepatic cytochrome (CY) P450 enzymes can increase the metabolism of sex hormones and make hormonal contraception ineffective. In addition, AEDs may even increase seizure frequency or severity or change the seizure type.